Neo-assyrian women revisited - Melville, Sarah C.; Svärd, Saana 1977- (2019)
In her recent book, Svärd uses theories of hierarchical and heterarchical power to reveal how women wielded power within the highest echelons of the Assyrian Empire Svärd determines that the queen occupied a distinct position in the state hierarchy, separate from the king, and that only one woman at a time could be queen. The queen could retain her post even after the king died, though the new king could replace her if he deemed it necessary. The king decided the queen mother's role, depending on political circumstances. Both queens and queen mothers ran large, lucrative estates and participated in religious ceremonies. During the Sargonid period, military units were attached to their households. In some official spheres of action, their power could be qualitatively similar to that of the king, and in a crisis, they could even act for him. Other women associated with the palace, such as royal daughters, female administrators, and workers, were more apt to develop power heterarchically, through petitions, negotiation, or communication networks.
Keywords: Rezension